1994
DOI: 10.1116/1.587571
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulations of a positive chemically amplified photoresist for x-ray lithography

Abstract: This article presents the results of the experimental and modeling study of a positive tone, chemically amplified photoresist, in application to x-ray lithography. Spectrophotometric titration, Fourier transform infrared spectroscopy (FTIR), and development rate monitor data were acquired and used as inputs for the modeling of the processes and pattern simulations. The exposure model assumes monomolecular decomposition upon radiation and corresponds to Dill’s model for a nonbleaching photoactive compound. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The subscripts including i and j and the superscripts including n are the indices of the spatial grids and the temporal steps, respectively. The reaction parameters k a and k D and the diffusion coefficient D (a short-hand notation for D H ) all have superscripts involving n in finite-difference equations (18) (18) to (20) are the reaction orders, not to be confused with the time-step index denoted by the superscript n.…”
Section: Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The subscripts including i and j and the superscripts including n are the indices of the spatial grids and the temporal steps, respectively. The reaction parameters k a and k D and the diffusion coefficient D (a short-hand notation for D H ) all have superscripts involving n in finite-difference equations (18) (18) to (20) are the reaction orders, not to be confused with the time-step index denoted by the superscript n.…”
Section: Formulationmentioning
confidence: 99%
“…(4) accounts for the acid loss mechanism which is modeled as a reaction with the reaction parameter k a and the reaction order m [20]. The temperature dependence of the reaction parameters of the acid loss mechanism is given by [20] …”
Section: Physical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences between the models largely lie in the description of the acid diffusion process and the detail in which the reaction kinetics are incorporated. Predictions from reaction-diffusion models have been compared with the total extent of reaction with FTIR data before development in several systems [7,8,[12][13][14]. Top loss deprotection experiments and comparison with different acid diffusion descriptions showed that Fickian diffusion cannot explain the experimental results [11].…”
Section: Introductionmentioning
confidence: 99%